Qualitative Exploration of EFL Students' Preferred Instructional Approaches by Native and Non-Native English Teachers - Tutut Indah Widyawati; Rohmani Nur Indah; Burhanudin Syaifulloh (Journal of English Language Studies, 2025)
The ongoing argument about the effectiveness of Native English-Speaking Teachers (NESTs) versus Non-Native English-Speaking Teachers (NNESTs) raises critical questions about students' preferences and the factors shaping their learning experiences. This study explores 10th-grade English as Foreign Language (EFL) students’ preferences for teaching approaches employed by NESTs and NNESTs. Using a qualitative research design, the study employed thematic analysis to examine data collected through Focus Group Discussions (FGDs) and structured interviews with 10 high school students experienced with both NESTs and NNESTs. Findings indicate that students preferred NESTs for clarity of explanation, pronunciation correction, and interactive activities, such as games and group work, which fostered engagement and independent learning. NNESTs, on the other hand, were valued for their structured reliance on course materials and relatable motivational stories. These preferences highlight complementary strengths, suggesting that a balanced integration of both teaching styles could enhance English language learning. The study contributes to the ongoing discourse on the role of native-speaker-ism in English education and calls for teacher training programs that emphasize the unique strengths of NESTs and NNESTs. Future research should include teacher perspectives and observational data for a more comprehensive analysis.